A bibliometric review of the most cited literature related to mining injuries. Issue 4 (19th May 2017) - Nowrouzi, Behdin; Rojkova, Margarita; Casole, Jennifer; Nowrouzi-Kia, Behnam
Abstract: This review analysed the top 56 annual and lifetime cited articles related to mining injuries. The number of annual and lifetime citations, year of publication, design, topic of focus, number of authors, and country of publication, were collected and reported. Cross-sectional studies were the most commonly used design type and the majority of the corresponding authors were from the United States. Lost-time injury as an outcome measure (73% of articles) was the most frequently discussed topic. The findings of this review article are designed to facilitate future research by revealing existing patterns and trends within the science.